2015
DOI: 10.11606/issn.1678-4456.v52i2p125-133
|View full text |Cite
|
Sign up to set email alerts
|

Chemical carcinogenesis by DMBA (7,12-dimethylbenzanthracene) in female BALB/c mice: new facts

Abstract: Polycyclic aromatic hydrocarbons are known carcinogens used in rodent experimental models. In this study, the carcinogen DMBA (7,12-dimethylbenzanthracene) was administered by gavage, diluted in corn oil, to female BALB / c mice at hebdomadary doses of 1 mg per animal for 1, 3, 6 or 9 weeks. Animals were weighed and monitored weekly until death. Remaining animals were euthanized at the age of 53 weeks. At necropsy, representative fragments of neoplasms were collected and routinely processed for histopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Studies with rodents receiving DMBA (1 mg/animal) during 1st, 3rd, 6th, or 9th week of treatment show that most (68%) histopathological changes, indicating this model as an important method to study carcinogenesis, which explains why doses of 1–3 mg are efficiently used in rodents to induce cancers . Indeed, DMBA is a carcinogenic chemical that requires metabolic activation in the liver and mammary gland .…”
Section: Discussionmentioning
confidence: 99%
“…Studies with rodents receiving DMBA (1 mg/animal) during 1st, 3rd, 6th, or 9th week of treatment show that most (68%) histopathological changes, indicating this model as an important method to study carcinogenesis, which explains why doses of 1–3 mg are efficiently used in rodents to induce cancers . Indeed, DMBA is a carcinogenic chemical that requires metabolic activation in the liver and mammary gland .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that DMBA causes breast enlargement, which was reduced with the CPA and CIT therapies. DMBA (1–20 mg/animal, single dose) for 6–13 weeks can cause mammary tumors in 75–100% experimental animals (Alencar et al, 2019; Currier et al, 2005; Oliveira et al, 2015). Our histopathological results suggest that DMBA (6 mg/kg/week) at the 11th weeks induced significant mammary carcinoma in the right breast of female mice.…”
Section: Discussionmentioning
confidence: 99%
“…(1-20 mg/animal, single dose) for 6-13 weeks can cause mammary tumors in 75-100% experimental animals (Alencar et al, 2019;Currier et al, 2005;Oliveira et al, 2015) (Sanchez-Diaz et al, 2008). CIT also induces genotoxicity (Bouslimi et al, 2008) and CA (Kuroda et al, 2013).…”
Section: (C)mentioning
confidence: 99%
“…Carcinogenesis induction was performed by single intradermal application of 0.5% DMBA (7,12-dimethylbenzanthracene, Sigma-Aldrich, USA) diluted in acetone to the skin of the dorsal region of the thorax, 3 cm in the caudal direction to the first cervical vertebra, as described by Oliveira et al 13 . Due to the safety of the team, the procedure was performed in a laminar flow chamber, with the use of individual protection (PPE).…”
Section: Induction Of Neoplasiamentioning
confidence: 99%